Analisis Laporan Keuangan Untuk Menilai Kinerja Keuangan Pada PT. Altek Metalinti Jaya Karawang Periode 2019-2021 - Syaifitri, Tiara (Peneliti.net, 2024)
This study aims to determine the financial performance at PT. Altek Metalinti Jaya for the 2019-2021 period in terms of liquidity ratios, solvency ratios, profitability ratios, and activity ratios. The type of research used in this research is quantitative research with a descriptive approach. The processed data is the company's financial statements PT. Altek Metalinti Jaya Period 2019-2021. The method of analysis utilized is called quantitative analysis, and it makes use of numerical data processing as a tool for conducting and interpreting investigations. The next step is a time series analysis, which compares financial ratios from one period to the next. The examination of financial ratios, including those for liquidity, solvency, profitability, and activity, is done using ratios. With the results of research on the liquidity ratio seen from the current ratio in good condition but on the quick debt ratio, the company is not in good condition, from the solvency ratio seen from the ratio of debt to assets and the ratio of debt to equity, the company is in good health, and from the profitability ratio seen from the gross profit margin ratio, net profit margin, operating profit margin, the company is experiencing financial condition instability and from the activity ratio seen from the asset turnover ratio, working capital turnover ratio, fixed asset turnover ratio, and inventory turnover ratio, the company is in a condition that good because the proportion in this ratio has increased every year.